Modelling Australia's exports of non-commodity goods and services - Michael Kouparitsas; Linden Luo; Jazmine Smith (The Australian Government, The Treasury, 2017)
This paper models both the supply and demand of Australian non-commodity exports. We derive long-run export demand relationships from first principles. On the demand side, the paper finds a relatively low substitution elasticity between Australian exports and a broad basket of foreign produced goods and services. So, for instance, if Australian export prices increase, overseas buyers are less likely to respond by purchasing the same goods and services from foreign competitors, and are instead more likely to respond by reducing their demand for the product – whether Australian or foreign-made. In other words, income effects trump substitution effects. This result is consistent with other Australian studies. On the supply side, our modelling assumes that Australian manufacturing and services exporters are price setters – an assumption consistent with existing literature. This means that if global input costs increase, Australian exporters are able to pass some of that increase onto their customers. Based on this assumption, our modelling suggests that labour costs are a larger contributor to Australia's non commodity export prices than imported intermediate inputs costs.
Keywords: C22; C53; F17; 330; Trade policy; optimal tariff; price elasticity; Public debt; debt dynamics; fiscal policy; debt sustainability; fiscal sustainability